2000
DOI: 10.1182/blood.v96.13.4091
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of soluble urokinase-type plasminogen activator receptor is a strong and independent predictor of survival in human immunodeficiency virus infection

Abstract: Human immunodeficiency virus-1 (HIV-1) infection has been shown to result in up-regulation of the urokinase-type plasminogen activator receptor (uPAR/CD87) on leukocytes in vitro and in vivo. The objective of this study was to investigate whether this up-regulation is paralleled by higher serum levels of soluble uPAR (suPAR) in patients with advanced HIV-1 disease and whether the serum level of suPAR is predictive of clinical outcome. Using an enzyme-linked immunosorbent assay, the level of suPAR was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(118 citation statements)
references
References 17 publications
6
108
1
3
Order By: Relevance
“…The present study demonstrated that suPAR levels are highly elevated and of prognostic value in patients with pneumococcal bacteraemia. Elevated suPAR levels have been shown previously to be of prognostic value for patients with various forms of malignant diseases [32][33][34][35][36], as well as with HIV-1 infection [15], urinary tract infection [37], tuberculosis infection [18], and bacterial meningitis [38]. Similarly, increased suPAR levels in the present study were a strong predictor of mortality.…”
Section: Discussionsupporting
confidence: 79%
“…The present study demonstrated that suPAR levels are highly elevated and of prognostic value in patients with pneumococcal bacteraemia. Elevated suPAR levels have been shown previously to be of prognostic value for patients with various forms of malignant diseases [32][33][34][35][36], as well as with HIV-1 infection [15], urinary tract infection [37], tuberculosis infection [18], and bacterial meningitis [38]. Similarly, increased suPAR levels in the present study were a strong predictor of mortality.…”
Section: Discussionsupporting
confidence: 79%
“…suPAR has previously been shown to predict mortality in treatment-na€ ıve HIV-1-infected patients [16]. In HIVpatients initiating ART, mortality was concentrated in the highest suPAR quartile, while patients with a low suPAR level had a low risk of mortality despite low CD4 cell count and low body weight [15].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our findings, Kofoed et al [19] showed that suPAR predicted outcome in patients with SIRS. Soluble form of the receptor is not a specific marker for bacterial infection or sepsis: an association has also been observed between high suPAR concentrations and mortality in patients with HIV [12,13], tuberculosis [15] and malaria [20]. In a study including 151 patients with SIRS (96 with bacterial infection), it was foundthatCRPandPCT,butnotsuPAR,couldbeused inthe diagnosis ofbacterial sepsis [16]; AUCvalues for CRP, PCT and suPAR were 0.81, 0.72 and 0.50, respectively.…”
Section: Discussionmentioning
confidence: 99%